Increased potency of recombinant VWF D′D3 albumin fusion proteins engineered for enhanced affinity for coagulation factor VIII. (17th August 2021) - Chia, Jenny; Pestel, Sabine; Glauser, Isabelle; Emmrich, Kerstin; Hardy, Matthew P.; Mischnik, Marcel; Raquet, Elmar; Tomasetig, Vesna; Claar, Philipp; Zalewski, Anton; Bass, Gregory T.; Turnbull, Victor; et al.
Abstract: Background: We have recently reported on a recombinant von Willebrand factor (VWF) D′D3 albumin fusion protein (rD′D3‐FP) developed to extend the half‐life of coagulation factor VIII (FVIII) for the treatment of hemophilia A. Based on predictive modelling presented in this study, we hypothesized that modifying rD′D3‐FP to improve FVIII interaction would reduce exchange with endogenous VWF and provide additional FVIII half‐life benefit. Objectives: The aim of this study was to identify novel rD′D3‐FP variants with enhanced therapeutic efficacy in extending FVIII half‐life. Methods: Through both directed mutagenesis and random mutagenesis using a novel mammalian display platform, we identified novel rD′D3‐FP variants with increased affinity for FVIII (rVIII‐SingleChain) under both neutral and acidic conditions and assessed their ability to extend FVIII half‐life in vitro and in vivo . Results: In rat preclinical studies, rD′D3‐FP variants with increased affinity for FVIII displayed enhanced potency, with reduced dose levels required to achieve equivalent rVIII‐SingleChain half‐life extension. In cell‐based imaging studies in vitro, we also demonstrated reduced dissociation of rVIII‐SingleChain from the rD′D3‐FP variants within acidic endosomes and more efficient co‐recycling of the rD′D3‐FP/rVIII‐SingleChain complex via the FcRn recycling system. Conclusions: In summary, at potential clinical doses, the rD′D3‐FP variants provide marked benefits with respect to dose levels and half‐life extension of co‐administered FVIII, supporting their development for use in the treatment of hemophilia A.